2006
DOI: 10.2165/00002018-200629030-00009
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Events Associated with Long-Term Use of Celecoxib, Rofecoxib and Meloxicam in Taiwan

Abstract: Patients taking celecoxib had a lower risk of cardiovascular events than those taking meloxicam. Patients taking rofecoxib were not found to be at higher cardiovascular risk than those taking meloxicam. The most significant determinant of cardiovascular risk was a history of such cardiovascular disease in the year preceding treatment initiation. Patients with a history of other medical conditions also appeared to be at higher risk of adverse cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Macrophages from Ind. COX-2 KOs revealed evidence consistent with substrate rediversion to the 5-lipoxygenase pathway with increased formation of their most abundant products, 5-HETE and LTC 4 . Thus, these mice may more closely correspond to those models described above in which 5-lipoxygenase induction accompanies further acceleration of atherosclerosis than observed with ApoE deficiency alone and in which the FLAP inhibitor MK 886 was effective.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Macrophages from Ind. COX-2 KOs revealed evidence consistent with substrate rediversion to the 5-lipoxygenase pathway with increased formation of their most abundant products, 5-HETE and LTC 4 . Thus, these mice may more closely correspond to those models described above in which 5-lipoxygenase induction accompanies further acceleration of atherosclerosis than observed with ApoE deficiency alone and in which the FLAP inhibitor MK 886 was effective.…”
Section: Discussionmentioning
confidence: 77%
“…Observational studies consistent with a cardiovascular risk have been reported for several traditional NSAIDs, which also exhibit selectivity for inhibition of COX-2, such as diclofenac and meloxicam (2)(3)(4)(5). The clinically manifest elements of this hazard (a predisposition to thrombotic events, an elevation of blood pressure, cardiac failure, and arrhythmogenesis) have been recapitulated in rodent models in which the COX-2-dependent formation of prostacyclin (PGI 2 ) or its action is disrupted (6)(7)(8).…”
mentioning
confidence: 78%
See 3 more Smart Citations